Revisited Hyperoxia Pathophysiology in the Perioperative Setting: A Narrative Review - Busani, Stefano; Sarti, Marco; Serra, Francesco; Gelmini, Roberta; Venturelli, Sophie; Munari, Elena; Girardis, Massimo (Frontiers in Medicine, 2021)
The widespread use of high-dose oxygen, to avoid perioperative hypoxemia along with WHO-recommended intraoperative hyperoxia to reduce surgical site infections, is an established clinical practice. However, growing pathophysiological evidence has demonstrated that hyperoxia exerts deleterious effects on many organs, mainly mediated by reactive oxygen species. The purpose of this narrative review was to present the pathophysiology of perioperative hyperoxia on surgical wound healing, on systemic macro and microcirculation, on the lungs, heart, brain, kidneys, gut, coagulation, and infections. We reported here that a high systemic oxygen supply could induce oxidative stress with inflammation, vasoconstriction, impaired microcirculation, activation of hemostasis, acute and chronic lung injury, coronary blood flow disturbances, cerebral ischemia, surgical anastomosis impairment, gut dysbiosis, and altered antibiotics susceptibility. Clinical studies have provided rather conflicting results on the definitions and outcomes of hyperoxic patients, often not speculating on the biological basis of their results, while this review highlighted what happens when supranormal PaO2 values are reached in the surgical setting. Based on the assumptions analyzed in this study, we may suggest that the maintenance of PaO2 within physiological ranges, avoiding unnecessary oxygen administration, may be the basis for good clinical practice.